EVALUATION OF THE REGULARITY OF ANTIHYPERTENSIVE DRUGS USAGE AS A COMPONENT OF TREATMENT ADHERENCE IN OUTPATIENTS OF A SPECIALIZED CARDIOLOGY CENTER - A. V. Kontsevaya; T. S. Romanenko; V. A. Vygodin; S.B B. Fitilev (Столичная издательская компания, 2015)
High adherence to blood pressure (BP) medical correction determines clinical and socioeconomic efficacy of antihypertensive treatment. Separate components of adherence are to be studied, including regularity of drugs intake and reasons for non-compliance with medical recommendations in different categories of patients.Aim. Evaluation of antihypertensive drugs (AHD) intake regularity (as a component of treatment adherence) and factors it is influenced by in hypertensive patients who had for the first time visited a specialized cardiology center during the 6-month follow-up after the primary consultation.Material and methods. First, a number of hypertensive patients who had visited a cardiologist of one of Moscow's district cardiology clinics for the first time in 2010 (n=1766) had formed a sample of the study participants. The expert cards were filled out in accordance with the primary medical documentation data. The second step was conducted 6 months after the first visit by a phone survey with the completion of questionnaires (n=1419).Results. Majority of respondents (74.9%) had been taking AHD regularly 6 months after the primary consultation and 16.2% of the patients had been using them occasionally. 8.9% of the respondents completely refused to control hypertension with drugs. Respondents of male sex (OR=1.4), with poor BP self-control in home settings (OR=2.5), unable to get drugs under the medicine assistance scheme (OR=1.8), those without coronary heart disease (OR=1.9), with hypertension duration less than 5 years (OR=1.9), with changes in antihypertensive therapy regimen as compared to the one recommended by a cardiologist (OR=1.5), those who had 1-2 drugs in the treatment regimen at the moment of the survey (OR=2.4) and patients who had no fixed drug combinations in the treatment scheme (OR=1.4) were shown to have significantly higher probability of irregular AHD intake or complete treatment refusal.Conclusion. Outpatients of the specialized cardiology center are characterized by rather high treatment adherence by AHD intake regularity. We have revealed a number of factors that significantly correlate with reduced antihypertensive treatment adherence. These factors must be taken into account at treatment regimen selection and patients' follow-up.